IDENTIFIKASI MISKONSEPSI SISWA PADA MATERI CAHAYA MENGGUNAKAN FOUR TIER DIAGNOSTIC TEST - Irianti, Erika (Universitas Pendidikan Ganesha, 2021)
A misconception is a problem that always arises in the world of education. Misconceptions occur in various fields of education, including the field of science, in this case science learning. This research was conducted to identify the misconceptions of students at the Junior High School level regarding light material. The approach used in this research is quantitative. The research was conducted at one of the state junior high schools in Indragiri Hilir Regency, Riau. The population in this study were students of class IX. The research sample was 25 students who had studied the material of light. Sampling using a purposive sampling technique. The data uses a four-tier diagnostic test instrument. Collecting data process uses google form. The results showed that students experienced misconceptions in the medium category with a proportion of 35.60%. Students experience the highest misconceptions on the following four concepts: 1) The properties of light; 2) Light Reflection; 3) The effect of the color of objects on the color of light; 4) the nature of polychromatic light as it passes through colored objects.